Hepatobiliary Phase Features of Preoperative Gadobenate-Enhanced MR can Predict Early Recurrence of Hepatocellular Carcinoma in Patients Who Underwent Anatomical Hepatectomy - Liu, Wanmin; Song, Kairong; Zheng, Wei; Huo, Lei; Zhang, Sisi; Xu, Xiaowen; Wang, Peijun; Jia, Ningyang (Frontiers in Oncology, 2022)
Purpose The purpose of this study was to establish a model for predicting early recurrence (≤ 2 years) of hepatocellular carcinoma (HCC) after curative resection based on the hepatobiliary phase (HBP) imaging characteristics of gadobenate-enhanced MRI. Methods A total of 155 patients who underwent curative resection HCC therapy and gadobenate-enhanced MRI were included retrospectively. The patients were divided into the early recurrence-free group (n = 103) and the early recurrence group (n = 52). Univariate and multivariate cox regression analysis was used to determine the independent risk factors related to early recurrence and four models were established. The preoperative model with/without hepatobiliary phase (HBP) imaging features (HBP-pre/No HBP-pre model) and the postoperative model with/without HBP imaging features (HBP-post/No HBP-post model). Bootstrap resampling 1000 times was used to verify the model and displayed by nomograms. The performance of nomograms were evaluated by discrimination, calibration and clinical utility. Net reclassification improvement (NRI) and Integrated discrimination improvement (IDI) were used to evaluate the differences between models and to select the optimal model. Results Shape, arterial peritumoral enhancement, AFP-L3 and peritumoral hypointensity on HBP were identified as independent risk factors. Prothrombin time (PT) and r-glutamyltransferase (GGT) were selected by multivariate Cox regression. These six factors construct the HBP-pre model. Removing peritumoral hypointensity on HBP was No HBP-pre model. Adding microvascular invation (MVI) and microscopic capsule factors were HBP-post and No HBP-post model. The C-index was 0.766, 0.738, 0.770 and 0.742 respectively. The NRI and IDI of HBP-pre vs No HBP-pre model and HBP-post vs No HBP-post model significantly increased 0.258, 0.092 and 0.280, 0.086. The calibration curve and decision curve analysis (DCA) had good consistency and clinical utility. However, the NRI and IDI of No HBP-post vs No HBP-pre model and HBP-post vs HBP-pre model did not increase significantly. Conclusions Preoperative gadobenate-enhanced MR HBP imaging features significantly improve the model performance while the postoperative pathological factors not. Therefore, HBP-pre model is selected as the optimal model. The strong performance of this model may help hepatologists to assess the risk of recurrence in order to guide the selection of treatment options.